KEMAMPUAN LOMPAT JAUH MENGGUNAKAN MEDIA â€œKBâ€ KELAS V SDN 11 DURIAN SEBATANG - Joharuddin, Udin (Universitas Tanjungpura, 2021)
Sports activity for grade V elementary school students is not an abstract experience. Therefore,Â the use of used cardboard props is very important to make it easier for students to learn theÂ long jump practice. One of the alternative props that can be used in the long jump practice isÂ used cardboard (KB). The purpose of this research is to find out that the use of used cardboardÂ props (KB) can improve the long jump ability of grade V students of SDN 11 Durian Sebatang,Â Seponti District, Kayong Utara Regency. After carrying out Classroom Action Research for 2Â cycles, in general it can be said that by using used cardboard props (KB) students' long jumpÂ abilities were quantitatively increased. In addition, the interest, attention, participation andÂ presentation of students also increased.